Economic Feasibility Analysis of Organic Farming Business as Part of Sustainable Agriculture - Judijanto, Loso; Lestari, Putu Fajar Kartika (Westscience Press, 2025)
This study analyzes the economic feasibility of organic farming as part of sustainable agriculture in Indonesia. Using a quantitative research design, data were collected from 75 respondents consisting of organic farmers and stakeholders. A structured questionnaire with a Likert scale (1–5) was employed, and data were analyzed using SPSS version 25, including descriptive statistics, validity and reliability testing, and multiple regression analysis. The results show that organic farming is economically feasible, with production costs, profitability, market access, and sustainability all exerting positive and significant influences on economic feasibility. The regression model explained 61.2% of the variance, with sustainability emerging as the strongest predictor, followed by profitability, production costs, and market access. These findings suggest that organic farming not only contributes to environmental sustainability but also provides tangible financial returns for Indonesian farmers. Policy implications highlight the need for government support in training, certification, market development, and financial incentives to strengthen the organic sector. The study concludes that organic farming can serve as a viable strategy for sustainable rural development in Indonesia, although challenges related to market access and certification remain.